The Potential of Creative Thinking in STEAM Based Science Learning: Supporting Factors and Implementation Challenges - Dini Fatrisia Hasniati; Raharjo Raharjo; Elok Sudibyo; Muhammad Satriawan (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aim to examine the factors causing low creative thinking skills in STEAM-based science learning, including indicators of creative thinking and various challenges in its implementation. Methodology: The research method used is a systematic literature review (SLR). Data collection uses the PRISMA flow. Data were obtained from the Sinta-indexed Google Scholar database for national journals and, for international journals, there were no restrictions; all journals were accessed through the Publish Or Perish (PoP) application. Data analysis used bibliometrics related to keyword accuracy and was visualized using VOS Viewer software. A total of 500 articles were obtained, of which 18 articles were used as primary data and as material for analysis in the discussion. Main Findings: The results showed that there were four indicators relevant to Guilford's theory regarding creative thinking skills in STEAM learning. Factors contributing to low creative thinking skills included lack of motivation, monotonous methods, models, and tasks, as well as the implementation of learning activities. Additionally, challenges in improving creative thinking skills in STEAM learning included long duration and the difficulty of improving fluency indicators. Novelty/Originality of this study: This study is novel because it structuredly examines the supporting factors and various implementation challenges in developing creative thinking skills through STEAM-based science learning. This research combines pedagogical, contextual, and professional perspectives from teachers, resulting in empirical findings that enrich STEAM studies and strengthen the application of creative thinking development strategies in science education.